2018
DOI: 10.1111/1365-2745.12979
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixer abundance has no effect on biomass recovery during tropical secondary forest succession

Abstract: Abstract1. Nitrogen-fixing trees (N 2 fixers) provide new nitrogen critical for rapid biomass accumulation of tropical forests during early secondary succession, but it remains unclear how the abundance of N 2 fixers in the forest community affects the growth of non-fixers or the primary productivity of the whole forest.2. On the one hand, N 2 fixers may enhance forest productivity by providing a facilitative effect through the provision of plant-available nitrogen to non-fixing trees. On the other hand, N 2 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 84 publications
1
29
1
Order By: Relevance
“…It also suggests that legumes do not share biologically fixed N and prefer to tolerate low level of soil N with a low N‐demanding lifestyle, which implies slow recycling rates. These results are consistent with recent findings in Panamanian forests which show that fixers do not have an effect on biomass recovery in secondary succession (Lai, Hall, Batterman, Turner, & Breugel, ). Future demographic data, such as growth and mortality rates, might provide evidence to test this finding.…”
Section: Discussionsupporting
confidence: 93%
“…It also suggests that legumes do not share biologically fixed N and prefer to tolerate low level of soil N with a low N‐demanding lifestyle, which implies slow recycling rates. These results are consistent with recent findings in Panamanian forests which show that fixers do not have an effect on biomass recovery in secondary succession (Lai, Hall, Batterman, Turner, & Breugel, ). Future demographic data, such as growth and mortality rates, might provide evidence to test this finding.…”
Section: Discussionsupporting
confidence: 93%
“…The Smithsonian Tropical Research Institute manages three blocks of land (664 ha total) within a 3 × 5 km area, of which ~530 ha was covered by fallow vegetation and secondary forests of various ages upon property acquisition in 2008. Successional trajectories and dynamics in plant diversity and composition in these forests have been extensively studied (Barry, Schnitzer, van Breugel, & Hall, 2015;Batterman et al, 2013;van Breugel et al, 2013;Craven, Hall, Berlyn, Ashton, & van Breugel, 2015Lai, Hall, Batterman, Turner, & van Breugel, 2018;Lai, Hall, Turner, & van Breugel, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…In contrast, some recent studies in moist tropical forests did not support the notion of N-fixing trees facilitating the growth or nutrient acquisition of neighboring plants during secondary succession [18] or any effect on the total biomass accumulation of the secondary forest [19]. Rather than depleting agroecosystem N capital, as happens in slash-and-burn systems due to gaseous losses of N during burning [5], the inclusion of N-fixing tree species to enhance N stocks in AFS requires continued validation.…”
Section: Introductionmentioning
confidence: 71%
“…One premise that supports the use of many forms of AFS is that the use of N fixers increases N availability in an agroecosystem, so these results are somewhat surprising. However, other recent research has similarly indicated that N-fixing trees may neither benefit nor inhibit neighboring trees [18] and may not confer a competitive or facilitative effect on secondary growth [19]. It may be necessary to convert N fixers into green manure to capture N benefits.…”
Section: Planted Tree Growthmentioning
confidence: 97%